2023
DOI: 10.3847/1538-4365/acc1de
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Analysis of Galactic Radio Supernova Remnants

Abstract: We present a revised table of 390 Galactic radio supernova remnants (SNRs) and their basic parameters. Statistical analyses are performed on SNR diameters, ages, spectral indices, Galactic heights, and spherical symmetries. Furthermore, the accuracy of distances estimated using the Σ–D relation is examined. The arithmetic mean of the Galactic SNR diameters is 30.5 pc with standard error 1.7 pc and standard deviation 25.4 pc. The geometric mean and geometric standard deviation factor of Galactic SNR diameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Compared to the known SNRs, the four newly identified SNRs have relatively flatter spectra, which may be due to background thermal emission or the fact that older SNRs tend to have flatter spectra (Bozzetto et al 2017). However, Ranasinghe & Leahy (2023) did not find such an age-spectral index relation. Since the older SNRs are usually very faint, there could be a large amount of them left to be discovered with more sensitive radio surveys.…”
Section: The Problem Of Missing Galactic Supernova Remnantsmentioning
confidence: 74%
“…Compared to the known SNRs, the four newly identified SNRs have relatively flatter spectra, which may be due to background thermal emission or the fact that older SNRs tend to have flatter spectra (Bozzetto et al 2017). However, Ranasinghe & Leahy (2023) did not find such an age-spectral index relation. Since the older SNRs are usually very faint, there could be a large amount of them left to be discovered with more sensitive radio surveys.…”
Section: The Problem Of Missing Galactic Supernova Remnantsmentioning
confidence: 74%
“…Motivated by the size constraints and luminosities of different source types and how they compare to FRB PRSs (see Figure 5), we investigate the phase space of radio luminosity and physical size of sources such as the known PRSs associated with FRBs; wandering black hole (BH) candidates in dwarf galaxies (Reines et al 2020;Sargent et al 2022); the compact radio source emerging from SN1986J's SNR at the epoch of maximum radio luminosity (Bietenholz & Bartel 2017); Galactic SNRs and PWNe 14 (Green 2019;Ranasinghe & Leahy 2023); SNRs in nearby galaxies with distances ranging from 0.055-14.5 Mpc (Urošević et al 2005); transient sources such as the PWN candidate VT 1137-0337 (Dong & Hallinan 2023) and the orphan GRB afterglow FIRST J141918.9 +394036 (Law et al 2018;Marcote et al 2019); PRS-like candidates identified in a low-frequency survey (Vohl et al 2023); and low-luminosity AGNe detected with the VLBA spanning a redshift range of z = 0.3-3.4 (Radcliffe et al 2018). We note that the sample of Galactic SNRs is nearly complete for remnant ages <2 kyr and shows a mean Galactic SNR diameter of 30.5 pc (Ranasinghe & Leahy 2023).…”
Section: Comparison With Other Sourcesmentioning
confidence: 99%
“…We scale the radio luminosities of sources to 1 GHz using their measured spectral indices from the literature. This excludes SNRs and PWNe as their flux densities are measured at 1 GHz (Ranasinghe & Leahy 2023). For sources without a measured spectral index, we assume a canonical value of α = −0.7 (Condon 1992;Gioia et al 1982).…”
Section: Comparison With Other Sourcesmentioning
confidence: 99%
“…Green (2019) has presented a sample of 294 Galactic SNRs. This list has been recently revised by Ranasinghe & Leahy (2023), who presented a revised table of 390 Galactic SNRs, however, some of them are SNR candidates. This is much smaller than the predicted population of a few thousand Galactic SNRs (Ranasinghe & Leahy 2022).…”
Section: Introductionmentioning
confidence: 99%